2014
DOI: 10.1017/s1365100514000066
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Wealth in the Blanchard–yaari Model

Abstract: We study the dynamics of the distribution of wealth in an economy with infinitely lived agents, intergenerational transmission of wealth, and redistributive fiscal policy. We show that wealth accumulation with idiosyncratic investment risk and uncertain lifetimes can generate a double Pareto wealth distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 16 publications
(18 reference statements)
4
49
1
Order By: Relevance
“…Benhabib et al (2014) derive the double Pareto distribution in an economy with optimizing agents subject to idiosyncratic investment risk, which is similar to my results. Although they have features absent in my model (bequest, fiscal policies, etc.…”
Section: Comparison To the Literaturesupporting
confidence: 83%
See 3 more Smart Citations
“…Benhabib et al (2014) derive the double Pareto distribution in an economy with optimizing agents subject to idiosyncratic investment risk, which is similar to my results. Although they have features absent in my model (bequest, fiscal policies, etc.…”
Section: Comparison To the Literaturesupporting
confidence: 83%
“…My results on the cross-sectional distributions build on and extend those of Gabaix (1999) and Benhabib et al (2011Benhabib et al ( , 2014. Benhabib, Bisin, and Zhu derive the power law in an equilibrium model with optimizing agents, which is closest to my results.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…A property that holds for the lognormal can often be generalized for dPlN. Second, Benhabib et al (2014) and Toda (2014) have theoretically shown that the size distribution of consumption should be approximately lognormal within age cohorts and double Pareto or dPlN in the entire cross-section. Therefore if we find that consumption is dPlN, we have an indirect evidence suggesting that the consumption dynamics obeys the generative mechanism of dPlN.…”
Section: Introductionmentioning
confidence: 99%